2018
DOI: 10.5114/pg.2018.79809
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence and risk factors of constipation in inpatient palliative care unit patients vs. nursing home residents

Abstract: IntroductionConstipation is one of the most frequent clinical and nursing problems both in palliative care patients and in nursing home residents.AimTo assess the occurrence of constipation and its risk factors in adult inpatient palliative care units versus nursing homes.Material and methodsAn epidemiological study was performed in an inpatient hospice and a nursing home.ResultsFifty-one hospice patients and 49 nursing home residents were included in the study. Cancer was the main clinical condition in 90% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…17 They are at higher risk of rapidly worsening constipation due to dehydration, rapid titration of opioids and reduced mobility. 18 While methylnaltrexone in the ambulatory setting has been studied as a maintenance therapy given every other day for two weeks, 10 our practice in the inpatient setting is to order it as a one-time dose in patients who have become constipated despite other laxative use, similar to Patel's group in ICU patients. 11 The response rate in our study was slightly lower than the 55-66% response rate found in ambulatory patients.…”
Section: Discussionmentioning
confidence: 99%
“…17 They are at higher risk of rapidly worsening constipation due to dehydration, rapid titration of opioids and reduced mobility. 18 While methylnaltrexone in the ambulatory setting has been studied as a maintenance therapy given every other day for two weeks, 10 our practice in the inpatient setting is to order it as a one-time dose in patients who have become constipated despite other laxative use, similar to Patel's group in ICU patients. 11 The response rate in our study was slightly lower than the 55-66% response rate found in ambulatory patients.…”
Section: Discussionmentioning
confidence: 99%
“…ilaçların kullanımı fazladır (5). Konstipasyonun ileri evre kanser hastalarındaki prevelansı ise opioid kullanımındaki artış ve hastaların performans durumunda bozulma sonucu (%40-90) oldukça yüksektir (18,19). Boland ve Elaine (2017)'nin kanser hastalarında opioidle ilişkili konstipasyon sıklığını değerlendirdikleri çalışmasında ileri evre kanser hastalarında konstipasyon görülme sıklığı %52, opioid tedavi gören ileri evre kanser hastalarında ise %87 olarak belirtilmiştir (20).…”
Section: Dokuz Eylül üNiversitesi Hemşirelik Fakültesi Elektronik Dergisiunclassified
“…While approximately one-third of older adults are affected by constipation, 5 this increases to over two-thirds of people admitted to specialist palliative care. 6,7 However, a longitudinal study found that admission to a specialist palliative care unit did not improve constipation symptoms, and prevalence significantly increased in the palliative care unit. 8 Specialist palliative care is offered within hospices in the United Kingdom for patients throughout the trajectory of a terminal illness, focused on improving quality of life through pain and symptom management, supporting the individual and their loved ones and advising on practical concerns.…”
Section: Introductionmentioning
confidence: 99%